Rethinking Globalization and Continuing Relevance of the aoStatea in Comparative Politics (Global Journal of Human-Social Science, 2012)
Comparative politics is one of the sub-fields within the academic discipline of political science as well as an approach to the study of politics and development across countries As a field of study comparative politics focuses on understanding and explaining political phenomena that take place within a state society country or political system However it should be noted that while the field of comparative politics continues to change over time it is important to note that its definition too changes This paper therefore provides a comprehensive debate on the ontology epistemology and methodology within the entire field of comparative politics with critical reflections on the continuing relevance of the states in a globalizing world As a critical reflection this paper is not wedded to any single world-view or conclusion about globalization As a whole this paper is guided by the proposition that despite the assault on the state from a number of directions its role will remain central to the study of comparative politics as well as in the contemporary era of globalization
Keywords: Comparative politics; Globalization; State; Third World “Without comparisons to make; the mind does not know how to proceed” (Alexis de Tocquevill